Tests for Tunnel 2 of the Cantareira Water Project for the Metropolitan Area of São Paulo – A Historical and Technological Review (Revista Brasileira Multidisciplinar, 2009)
This article relates a work that was carried out between the end of the 1960's and the beginning of the 1970's, by the Chair of Fluid Mechanics (precursor of the Departamento de Hidráulica e Saneamento of the Escola de Engenharia de São Carlos – Universidade de São Paulo), with the objective of foreseeing the water flow rate at Tunnel 2 of the Cantareira Water Project for the Metropolitan Area of São Paulo. An original test using air circulation was carried out in the tunnel. Methods and techniques were developed in order to verify the flow rate and check its size, to guarantee 33 m3 /s of flow. The documents produced by the authors of the test were surveyed, organized chronologically and analyzed, seeking to infer the theoretical influences that had guided the methodologies, to describe the techniques and technologies and to analyze, in accordance with the document registers, the execution and the results reached by the tests.
Keywords: Tests of the tunnel for water flow rate; Sistema Cantareira; Historical review.